Anosognosia for cognitive and behavioral symptoms in Parkinson's disease with mild dementia and mild cognitive impairment: Frequency and neuropsychological/neuropsychiatric correlates. (September 2018) - Orfei, Maria Donata; Assogna, Francesca; Pellicano, Clelia; Pontieri, Francesco Ernesto; Caltagirone, Carlo; Pierantozzi, Mariangela; Stefani, Alessandro; Spalletta, Gianfranco
Abstract: Introduction: Anosognosia is a multidimensional phenomenon with detrimental effects on patients' illness course, therapy compliance and quality of life. We aimed at investigating anosognosia for cognitive and behavioral symptoms in Parkinson's Disease (PD) with dementia (PDD) and, for the first time, in PD with Mild Cognitive Impairment (MCI-PD). Methods: Community dwelling subjects (47 mild PDD, 136 multidomain MCI-PD (mdMCI-PD), 5 single domain MCI-PD (sdMCI-PD), and 197 PD without cognitive impairment (noCI-PD) were enrolled in a cross-sectional design study. All the subjects were administered the Anosognosia Questionnaire for Dementia, the Mental Deterioration Battery and a number of neuropsychiatric inventories. Results: A diagnosis of anosognosia was made in 36% of patients with mild PDD and 16% with mdMCI-PD, whether it was negligible in sdMCI-PD and noCI-PD. Higher severity of anosognosia for cognitive impairment was also found in PDD and in mdMCI-PD. SdMCI-PD had the lower severity of anosognosia for cognitive impairment. Higher anosognosia for cognitive impairment was associated to lower depression in noCI-PD (r = −0.227, p = 0.0013) and mdMCI-PD (r = −0.266, p = 0.0016), and to reduced hedonic tone in noCI-PD (r = −0.191, p = 0.0071). Greater anosognosia was associated to lower executive performances in PDD (r = 0.424, p = 0.0074). Conclusions: Anosognosia for non-motor symptoms is frequent in PD patients with mild dementia or mdMCI. Results confirm the role of neuropsychiatric characteristics in anosognosia also in PD, the high prevalence of anosognosia in neurodegenerative illnesses and suggest a common pathogenic path for anosognosia in different neurodegenerative and psychiatric disorders. Highlights: We investigated anosognosia for cognitive symptoms in PD with dementia and MCI. Higher anosognosia was related to higher cognitive impairment. Reduced anosognosia was linked to increased depression and reduced hedonic tone. In PDD anosognosia for cognitive deficits was related to poor executive functions. Our data support the hypothesis of trans -nosological models of anosognosia.